In vitro activity of the novel antifungal compound F901318 against Australian Scedosporium and Lomentospora fungi. (22nd January 2018) - Biswas, Chayanika; Law, Derek; Birch, Michael; Halliday, Catriona; Sorrell, Tania C; Rex, John; Slavin, Monica; Chen, Sharon C-A
Abstract: We determined the in vitro activity of the novel orotomide antifungal, F901318, against 30 Lomentospora prolificans, 20 Scedosporium apiospermum, 7 S. aurantiacum, and 3 S. boydii, isolates in comparison with standard antifungals. Against L. prolificans, F901318 was the most potent compound (MIC90 0.25 μg/ml); the geometric mean MIC (0.26 μg/ml) was significantly lower (23–80-fold) than those of itraconazole, voriconazole, posaconazole, and isavuconazole (all P < .001), and amphotericin B ( P < .05). F901318 also had good activity against S. apiospermum, S. aurantiacum, and S. boydii, comparable to that of voriconazole and posaconazole but was more active than isavuconazole for all three species.